Michael Riffaterre: Intertextuality, l’aporie Littéraire, Aesthetics, and Semiotics - Malau, Reynhard; Yappo, Yohanes; Pernando, Rendy; Veronica, Maria; Nainggolan, Andani; Timotius, Frenky Albert (Lingua : Journal of Linguistics and Language, 2023)
This study was motivated by the researchers' curiosity about Michael Riffaterre's thoughts on the use of semiotics in poetry. Several previous researchers have also applied Riffaterre's theorem to song lyrics, poems, poetry, and local wisdom in various contexts. However, some of these researchers did not provide a complete presentation of Riffaterre's semiotic instruments, despite their involvement in various language-forming contexts. For instance, this research employs a qualitative research method using a literature search model. The language used is clear, objective, and value-neutral, with a formal register and precise word choice. The literature study involves secondary sources, such as recently published journals, that discuss semiotics. Semiotics is not limited to poetry, but also includes song lyrics, poetry, and local wisdom. The structure is clear and logical, with causal connections between statements. The results indicate that semiotics is closely linked to tragedy and must consider various aspects such as anatomy, anthology, coherence, logic, plausibility, reductionism, amazement, connotation, expression of desolation, natural and constructed hypotheticals, opposition, silence, solitude, mimesis and comprehensiveness.